The Social Factor of Second Language Acquisition on Adult Learner - Sri Aulia Samosir; Sholihatul Hamidah Daulay; Khairun Niswa (PRASASTI: Journal of Linguistics, 2023)
Second language learning for adults is an activity to help adults in acquiring a second language is done consciously. The learning process for an adult second language is unfounded educator considerations but based on interests learners. Educational implications for practical adults is a necessary understanding of characteristics of adult education, principles, methods, and learning techniques second language for people mature. The purpose of this study is to find out the social factor in the classroom influence second language acquisition in adult learners. The researcher found there are classroom situations, namely: Teachers' strategy, students’ personality include (Motivation, introversion/ extroversion, self-esteem, inhibition, risk-taking, anxiety), and learning the English language as a part of a group.